Adherence to the monitoring of metabolic syndrome in patients receiving antipsychotics in outpatient clinics in Saudi Arabia - Feras A. Al-Awad; Hussien A. Almutairi; Saad A. Almutairi; Othman S. Alessa; Salman F. Alanazi; Nasser M. Alzain; Dalal M. Albakr; Safa I. Alzahrani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Monitoring protocols have been developed because patients taking atypical antipsychotics are more prone to developing metabolic syndrome, which leads to possible increased mortality and morbidity. The aim of this study was to assess the degree of adherence to the recommendations of metabolic syndrome monitoring. MATERIALS AND METHODS: This study was conducted in two large psychiatric facilities in the Eastern Province of Saudi Arabia. A retrospective analysis of the medical records of 350 patients taking antipsychotic medications was done, and an assessment was made of the frequency of metabolic monitoring at each of the intervals as suggested by the American Diabetes Association. Data was analyzed using SPSS; descriptive statistics. were computed and Chi-square test was used to determine statistical significance for association between categorical variable. RESULTS: The mean age of the patients was 34.9 ± 18 years; 64.6% were males. Olanzapine was the most prescribed medication (43.7%, n = 153), followed by quetiapine (17.4%, n = 61). Only one-third of the patients (29.6%) completed all the baseline parameters. Documentation of baseline parameters was low for glucose level (38.9%), lipid panel (17.3%), weight (25.2%), and waist circumference (1.4%). Adherence to yearly monitoring was much lower than at baseline (mean percentage: 29.6% vs. 1.7%). Furthermore, 45% of the patients were classified as obese and 10% had metabolic comorbidity. CONCLUSION: Individuals with mental illness who were taking antipsychotics did not undergo proper metabolic screening during antipsychotic treatment. Barriers to adherence to the monitoring guidelines should be examined and addressed. Giving assistance to practitioners to recall the required laboratory tests and vitals at certain intervals could help improve metabolic monitoring practices.